1988
DOI: 10.1085/jgp.92.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic free calcium, myosin light chain phosphorylation, and force in phasic and tonic smooth muscle.

Abstract: The time course of [Ca~+]i, tension, and myosin light chain phosphorylation were determined during prolonged depolarization with high K + in intact tonic (rabbit pulmonary artery) and phasic (longitudinal layer of guinea pig ileum) smooth muscles. [CaZ+]i was monitored with the 340 nm/380 nm signal ratio of the fluorescent indicator fura-2. The fluorescence ratio had a similar time course in both muscle types during depolarization with 109 mM [K+]o; after a transient peak, there was a decline to 70% of its pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(63 citation statements)
references
References 37 publications
7
56
0
Order By: Relevance
“…In the presence of high K+, MLC phosphorylation transiently increased and then decreased to a level near the resting level. This result is similar to the observation by Himpens et al (29). Our results showed that Li+ inhibited the high K+-induced increase in MLC phosphorylation.…”
Section: Permeabilized Musclesupporting
confidence: 93%
“…In the presence of high K+, MLC phosphorylation transiently increased and then decreased to a level near the resting level. This result is similar to the observation by Himpens et al (29). Our results showed that Li+ inhibited the high K+-induced increase in MLC phosphorylation.…”
Section: Permeabilized Musclesupporting
confidence: 93%
“…In summary, this study presents evidence that rapid increases in [Ca 2ϩ ] i in smooth muscle (13,25,35) induced by the stimulus, KCl, activates two distinct, temporally separated events: 1) the well-established activation of MLC kinase causing rapid, strong increases in MLC phosphorylation and cross-bridge cycling, producing a peak contraction (5,13,33), and 2) Ca 2ϩ -calmodulin-activated increases in ROK translocation to caveolae, leading to maintenance of tonic force (shown here). In conclusion, these data support the hypothesis that any stimulus that increases [Ca 2ϩ ] i in arterial muscle will cause increased ROK translocation to caveolae at the cell periphery, where additional signaling events, such as activation of ZIP-like kinase (20), that lead to sustained MLC phosphorylation and force in the face of temporally falling [Ca 2ϩ ] i may be coordinated.…”
Section: Effect Of Nifedipine and Tfp On The Ability Of Kclmentioning
confidence: 52%
“…Elevated intracellular calcium (Ca i 2ϩ ) levels stimulate smooth muscle contraction (17), and Ca o 2ϩ is required for the maintenance of myogenic tone (14), the intrinsic contractile activity of arterial wall smooth muscle that represents an important determinant of vascular resistance. The response to Ca o 2ϩ varies between artery type with some tissues showing contraction and others relaxation (3, 22, 35, 49 -51), but, in either case, these studies demonstrate that arteries can sense changes in [Ca 2ϩ ] o .…”
mentioning
confidence: 99%